Origins and Evolution of the α-L-Fucosidases: From Bacteria to Metazoans - You, Jia; Lin, Shujin; Jiang, Tao (Frontiers in Microbiology, 2019)
α-L-fucosidases (EC 3.2.1.51, FUC) belonging to glycoside hydrolase family 29 (GH29) play important roles in several biological processes and is recognized as a marker for detecting hepatocellular carcinoma. In this study, protein sequence similarity network (SSN) and evolutionary analysis were performed to understand the enzymes comprehensively. SSN indicated that the proteins in FUC family are mainly present in bacteria, fungi, Metazoa, and plants, but less in archaea. The sequences in bacteria are much diverse compared that in other taxonomic groups. SSN together with phylogenetic tree supported that the proteins in FUC family can be classified into 5 subfamilies. The multiple sequence alignments results indicated that the amino acid residues for binding α-L-fucosidase and catalysis are highly conserved in both bacteria and Metazoa, however, the evolutionary patterns were different based on the coevolution analysis. Because the enzymes from bacteria and Metazoa fall in the same subfamily, we proposed that the ancestral gene encoding α-L-fucosidase appeared before bacteria and eukaryotes diverged and bacterial and Metazoa α-L-fucosidases share a common ancestor. Finally, gene duplication plays an important role for α-L-fucosidase evolution not only in Metazoa but also in bacteria and fungi.